ANATOMICAL FEATURES AND DEVELOPMENTAL CHANGES IN THE BRONCHIAL STRUCTURE IN YOUNG ADULTS AGED 17-21 YEARS: AN ANATOMICAL STUDY - Usubjanov Oybek Bahromjon o’g’li; Sadiqova Zumrad Shavkatovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The bronchial tree, a critical component of the respiratory system, undergoes subtle yet significant anatomical changes during late adolescence (17-21 years), transitioning toward full adult maturity. This study investigates the anatomical features, dimensional variations, and developmental modifications in the bronchial structure among young adults in this age group. Utilizing cadaveric dissections and imaging techniques, we analyzed bronchial lengths, diameters, branching patterns, and wall thicknesses in 50 subjects. Results indicate progressive enlargement of bronchial lumens and increased cartilage density, correlating with pubertal growth spurts. These findings underscore the importance of age-specific normative data for clinical applications in respiratory medicine, such as bronchoscopy and pulmonary disease diagnosis. The study highlights potential implications for understanding respiratory vulnerabilities in young adults.